APPLYING PEER TEACHING TECHNIQUE TO IMPROVE STUDENTS’ GRAMMAR ACHIEVEMENT - Sembiring, Novalina (Kairos English Language Teaching Journal, 2021)
This study was aimed to improve the students’ grammar achievement, especially in using conditional sentences by applying peer teaching technique. The subject of the study was the third semester students of English Education Study Program in academic year 2017/ 2018. This study was conducted by applying Classroom Action Research (CAR) which had been conducted in two cycles and each cycle consisted of three meetings. The instruments of collecting data were quantitative data (grammar test and questionnaire) and qualitative data (observation checklist and fieldnotes). The results of the test showed that the mean score of pre test was 15, formative test was 35 and post test was 63. The result of observation checklist and fieldnotes showed that the students were interested in teaching and learning conditional sentences by applying peer teaching technique. These indicated that there was a significant improvement of the students’ grammar achievement by applying peer teaching technique.